Experimental Investigation of Mechanical Properties of ASTM A992 Steel at Elevated Temperatures - Lee, Jinwoo; Morovat, Mohammed A.; Hu, Guanyu; Engelhardt, Michael; Taleff, Eric M. (Engineering Journal, 2013)
This paper presents the results of a detailed experimental study into the mechanical properties of ASTM A992 structural steel at elevated temperatures. Critical testing issues, including temperature measurement, temperature control, and extensometer use along with the testing equipment and procedures are briefly explained. Tensile steady-state temperature tests are conducted on samples of ASTM A992 steel at temperatures up to 1000 °C. Full stress-strain curves, representing steel coupons tested to fracture at elevated temperatures, are generated. Important mechanical properties such as yield stress, tensile strength, proportional limit, elastic modulus and elongation are obtained from the stress-strain curves. Results are compared with elevated-temperature properties specified by Eurocode 3 and by the AISC Specification. When defined as the stress at 2% total strain, the measured yield stress values agree reasonably well with the corresponding values from Eurocode 3 and the AISC Specification. However, for more conventional definitions of yield stress, such as the 0.2% offset yield stress, the agreement is poor. It is observed that the yield stress of steel at elevated temperatures up to about 600 °C is highly dependent on the manner in which yield stress is defined. The effects of displacement loading rates on steel strength and static yielding behavior are also investigated. It is shown that the displacement rate has a large impact on the steel strength at elevated temperatures, especially at temperatures higher than 600 °C. Further work is needed to fully characterize the time-dependent effects on the elevated-temperature stress-strain response of structural steel. Additionally, this paper presents results of Charpy V-Notch (CVN) tests on ASTM A992 steel at elevated temperatures.